The bifurcation of aesthetic pleasure in the poetry of Abu Nawas - عيسى حكمت; كبَّابة وحيد; سليمان هنادي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Citizens of beauty and majesty emerge in the poetry of Abu Nawas by clarifying his aesthetic vision that was expressed in his poems, especially that literary aesthetics deals with the structure of artistic work, and this structure is embodied only through the awareness of written references and verbal and rhythmic sounds, and Abu Nawas was able to submit things The mental relationships of his deep philosophy, he added to the elements of aesthetic images philosophical visions brought him out of the ordinary, and his philosophy showed the aesthetic dimension in his poetry, and the Jalali side as well.